Green jobs: Potential for employment in the Republic of Serbia - Simonida Vukadinović; Jelena Ješić (Anali Ekonomskog fakulteta u Subotici, 2020)
This paper puts emphasis not only on employment problems but also on perspective of increasing employment rate in the Republic of Serbia (Serbia) in the field of circular economy. Circular economy, the 21 century concept and model, is a great chance for making employment rate higher, as well as for ecological protection and budget savings. This topic is very important for the Republic of Serbia (Serbia), candidate for the European Union (EU), and in that context greening economy is obligatory. What is one of the key measures for increasing of (green) employment is the state aid for training of employees, and strategic approach in that sense.